Atención al usuario en el Gad municipal del cantón San Francisco de Puebloviejo - Villamar Sánchez, Manuel Enrique (2019)
The present investigation reveals the problems that currently exist with regard to customer service in the Autonomous Decentralized Municipal Government of the San Francisco de Puebloviejo canton since users are dissatisfied with the attention they receive from public servants. The current case study is framed in the subject of customer service where it has been developed with the concepts of different authors that highlight guidelines to improve prior to the situation presented, it should be mentioned that the results obtained from users are evidenced in This document for a better interpretation in this document, concluding that the attention is unsatisfactory